Derrame de crudo y los impactos socioambientales ocurridos en la Comunidad Nativa la Petrolera, quebrada patoyacu, distrito de Urarinas, provincia de Loreto Nauta 2023 - Ruiz Rios, Rene (2024)
The research The research “Socio-environmental factors of the crude oil spill in the La Petrolera native community, Urarinas district – Chambira river – Patoyacu ravine - 2023” aimed to know the socio-environmental factors that influence the crude oil spill in the La Petrolera native community, district of Urarines. The research had a qualitative approach, descriptive level ethnographic design, the population is made up of 400 inhabitants (100 families) the sample is made up of 50% of families (50 heads of family) of the total population, made up of heads of family, authorities and key informants from the native community of La Petrolera, where interview and direct observation techniques were applied. The results indicate that the native community Urarina La Petrolera, in recent years, has suffered an oil spill in its territory, the last one was in 2018, which generated social and environmental changes that are reflected in their levels of relationship, communication and information between the community members, the State and the oil company, which was not good, because they did not comply with the established agreements, which generated unrest and conflicts. Finally, the work concludes the importance of the communal organization, which seeks the support and advice of the federation to which it belongs, seeking immediate solutions and asserting its rights as an indigenous community and use of its territories considered sacred and heritage of its ancestors.